The surtitle translation of cultural references : the face of Chiang Kai-Shek as a case study - Song, Shuang (Nanyang Technological University, 2020)
Drama surtitling is an interdisciplinary subject involving the areas of Audio Visual Translation(AVT), Theatre Studies, Literary Adaptation, Theatre Technology and so on. With the development of technology and increasing popularity of drama and other cultural events among the public, more attention is drawn to this area of research. However, drama surtitling is not sufficiently studied in terms of the considerations, strategies, and recommendations for practitioners. In translation studies, cultural references, i.e. the terms and expressions used to refer to the specific culture, are considered of high research significance for its key role in the cultural transfer. This research seeks to explore the challenges and corresponding strategies to translate cultural references in drama surtitles from Chinese to English. It is based on a case study of The Face of Chiang Kai-shek (蒋公的面子) written by Wen Fang-yi, which enjoys great popularity among Chinese audience and received multiple awards. The stage play contains many terms and expressions with extended cultural and historical meaning. Translating these cultural references in drama surtitles is faced with various constraints. The research data, i.e. the target text(TT) is translated by the researcher herself. The challenges are mainly introduced by the temporal and spatial constraints and the mode of operation including the word limit, line breaks, and caption grouping. Corresponding strategies to handle the challenges include dynamic equivalence, elaboration, domestication, omission and using abbreviation with the glossary in performance pamphlets.